Pelayanan Informasi Obat dalam Layanan Telefarmasi pada Apotek X Kota Mataram - Mayada, Silhiyatun; Mahacita Andanalusia; Eskarani Tri Pratiwi; Fara Mutia Bimantika; Lalu M. Rifqi Azami S (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Telepharmacy is an innovation in remote pharmaceutical services that has become increasingly relevant along with the rapid development of information and communication technology in the healthcare sector. This service enables pharmacists to continue providing optimal pharmaceutical care without direct face-to-face interaction. This study aimed to describe the implementation of drug information services provided by pharmacists through telepharmacy at Pharmacy X in Mataram City and to evaluate their compliance with pharmaceutical service standards as regulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 73 of 2016. This study employed a descriptive design with a cross-sectional approach, involving 40 patient interactions conducted via WhatsApp over a one-month period. The collected data included the types of medicines purchased by patients and the forms of drug information provided by pharmacists. The medicines were classified according to therapeutic categories, while drug information was analyzed using indicators based on pharmaceutical service regulations. The results showed that the most frequently purchased medicines were respiratory system drugs (26.67%), analgesic/antipyretic drugs (22.22%), and medicines for dyspepsia (17.78%). The most commonly provided drug information included dosage instructions (71.74%), explanations of special dosage forms (87.5%), and duration of use (54.35%). However, information regarding side effects (13.04%) and drug interactions (10.87%) was still limited. All patients receiving antibiotics were educated to complete their medication as prescribed (100%). Overall, drug information services delivered through telepharmacy at Pharmacy X were in accordance with pharmaceutical service standards, although improvements in clinical education are still needed to strengthen the quality and safety of digital pharmacy services.